Early onset pseudoxanthoma elasticum. Case report. - Kuru, B.C.; Koska, M.C.; Çobanoğlu Simşek, B.; Zindancı, İ. and Kavala, M. (European Journal of Pediatric Dermatology, 2017)
Pseudoxanthoma elasticum is a rare, autosomal recessive disorder affecting skin and internal organs and systems including eyes and cardiovascular system. Cutaneous findings can start in childhood; however, the diagnosis is usually confirmed in the fourth-fifth decade. Here is reported an 11 years old boy with pseudoxanthoma elasticum whose cutaneous findings started at the age of two; the diagnosis was confirmed at the age of eleven. Furthermore, there was no sign of systemic involvement. Cutaneous lesions can occur on atypical regions in the first years; this is why an early diagnosis is essential.